(untitled) (Research, Society and Development, 2022)
The quality of a highway interferes with the country’s economy and can be related to several aspects. This quality is evaluated by the functional condition of road paving. This research aims to analyze the influence of the management and jurisdiction of the highways on their functional quality. In this study, the Mann-Whitney statistical test was used to verify the existence of a significant difference between the samples of highways with different jurisdictions and management. In assessing the quality of roads, were used the aspects of the general condition of the road and pavement, the condition of the pavement surface, and traffic speed due to the pavement, according to a survey by the National Transport Confederation. It was found that there is a superiority of the evaluation indices of the highways of federal jurisdiction when compared to the state ones, but this difference was not significant when compared to the respective managements of these classes of highways.